Orphan Glutamate Receptor delta-1 Subunit Required for High-Frequency Hearing - Gao, Jiangang; Maison, Stephane F.; Wu, Xudong; Hirose, Keiko; Jones, Sherri M.; Bayazitov, Ildar; Tian, Yong; Mittleman, Guy; Matthews, Douglas B.; Zakharenko, Stanislav S.; Liberman, M. Charles; Zuo, Jian (East Carolina University, 2007)
The function of the orphan glutamate receptor delta subunits (GluR 1 and GluR 2) remains unclear. GluR 2 is expressed exclusively in the Purkinje cells of the cerebellum, and GluR 1 is prominently expressed in inner ear hair cells and neurons of the hippocampus. We found that mice lacking the GluR 1 protein displayed significant cochlear threshold shifts for frequencies of >16 kHz. These deficits correlated with a substantial loss of type IV spiral ligament fibrocytes and a significant reduction of endolymphatic potential in high-frequency cochlear regions. Vulnerability to acoustic injury was significantly enhanced; however, the efferent innervation of hair cells and the classic efferent inhibition of outer hair cells were unaffected. Hippocampal and vestibular morphology and function were normal. Our findings show that the orphan GluR 1 plays an essential role in high-frequency hearing and ionic homeostasis in the basal cochlea, and the locus encoding GluR 1 represents a candidate gene for congenital or acquired high-frequency hearing loss in humans. Originally published Molecular and Cellular Biology, Vol. 27, No. 12, June 2007
Keywords: Orphan glutamate receptor; High-frequency hearing loss; Ionic homeostasis; Basal cochlea